2015
DOI: 10.1371/journal.pone.0128693
|View full text |Cite
|
Sign up to set email alerts
|

Diorcinol D Exerts Fungicidal Action against Candida albicans through Cytoplasm Membrane Destruction and ROS Accumulation

Abstract: Candida albicans, which is the most common human fungal pathogen, causes high mortality among immunocompromised patients. Antifungal drug resistance becomes a major challenge for the management of Candida infection. Diorcinol D (DD), a diphenyl ether derivative isolated from an endolichenic fungus, exerted fungicidal action against Candida species. In this study, we investigated the possible mechanism of its antifungal activity. The change of membrane dynamics and permeability suggested that the cell membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 37 publications
0
58
0
1
Order By: Relevance
“…33 We found that treatment of C. albicans ATCC 10231 (strain A ) with compounds 4F and 7Aa at their 1× and 2× MIC values increased intracellular ROS production in this fungal strain (Figure 2). As expected, the H 2 O 2 positive control (at 1 mM) also induced ROS production in yeast cell, whereas no ROS induction was observed with untreated yeast cells (negative control).…”
Section: Resultsmentioning
confidence: 81%
“…33 We found that treatment of C. albicans ATCC 10231 (strain A ) with compounds 4F and 7Aa at their 1× and 2× MIC values increased intracellular ROS production in this fungal strain (Figure 2). As expected, the H 2 O 2 positive control (at 1 mM) also induced ROS production in yeast cell, whereas no ROS induction was observed with untreated yeast cells (negative control).…”
Section: Resultsmentioning
confidence: 81%
“…FLC treatment also enhanced ROS production, especially in the 5 and 50 μg/mL groups 25 . In another study, Li et al showed that treatment with 8 μg/mL of AMB significantly increased the ROS production in C. albicans 26 . According to the literatures and our experiment results, we used 25 μg/mL FLC or (and) 2 μg/mL AMB as positive controls for the antifungal mechanism research in the current study.…”
Section: Discussionmentioning
confidence: 95%
“…In order to determine if bisbenzimidazoles are capable of inducing ROS, we investigated the effect of two of our best compounds, 2 and 9 , against C. albicans ATCC 10231 (strain A ) in a dose depend manner at 1× and 2× MIC using a 2',7'-dichlorodihydrofluorescein diacetate (DCFH-DA) dye. 39 Generally, ROS is generated in mitochondria of eukaryotic cells as a byproduct during cellular metabolism. Cells neutralize the excess ROS production by activating their antioxidant functions.…”
Section: Resultsmentioning
confidence: 99%